How East New York became a ghetto - Thabit, Walter (New York University Press, 2003)
In response to the riots of the mid-'60s, Walter Thabit was hired to work with the community of East New York to develop a plan for low- and moderate-income public housing. In the years that followed, he experienced first-hand the forces that had engineered East New York's dramatic decline and that continued to work against its successful revitalization. How East New York Became a Ghetto describes the shift of East New York from a working-class immigrant neighborhood to a largely black and Puerto Rican neighborhood and shows how the resulting racially biased policies caused the deterioration o.